PP.30.27: OBESITY AND METABOLIC ABNORMALITIES IN YOUTH. (June 2015) - Redon, P.; Alvarez, J.; Guixeres, J.; Cantero, L.; Torro, I.; Lurbe, E.
Abstract : Objective: Therapies currently implemented for obesity are focused on nutritional aspects and on physical activity. In order to make physical activity a positive therapy instead of triggering disabilities it is relevant to accurately assess cardiovascular fitness. To assess the cardiovascular fitness by measuring the oxygen peak (VO2 peak) consumption and its relationship with classical cardiometabolic parameters in youth. Design and method: A modified Balke protocol was applied to eighty-three obese normotensive Caucasians (60% males), ranging from 9 to 16 years old, who underwent an assessment of cardiometabolic risk. Obesity was defined as higher than or equal to the 95th percentile for age and sex, and degree of obesity using BMI z-score. The control group consisted of forty-three non-obese, healthy, age and sex matched subjects, who were invited to participate from the general population. Results: The general characteristics of the population are shown in the Table. Significant differences in consumption of VO2 peak between controls and obese individuals were observed. However, no significant differences existed between degrees of obesity. In all subjects, VO2 peak was significant and inversely related with the anthropometric parameters BMI (r = -0.399, p = 0.000) or BMI Z-score (r = -0.470; p = 0.000), and insulin (r = -0.309; p = 0.01), and HOMA index (r = -0.297; p = 0.01). Figure. No caption available. Conclusions: The consumption of oxygen peak is a relevant clinical parameter that should be included in the routine clinical assessment of cardiometabolic risk in obese youth since it gives additional information of its metabolic status.